2001
DOI: 10.1007/s004410100447
|View full text |Cite
|
Sign up to set email alerts
|

Onset and time course of apoptosis in the developing zebrafish retina

Abstract: In mammalian development, apoptosis spreads over the retina in consecutive waves and induces a remarkable amount of cell loss. No evidence for such consecutive waves has been revealed in the fish retina so far. As the zebrafish is of growing importance as a model for retinal development and for degenerative retinal diseases, we examined the onset and time course of apoptosis in the developing zebrafish retina and in adult fish. We found that apoptosis peaked in the ganglion cell layer (GCL) and inner nuclear l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
78
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(92 citation statements)
references
References 32 publications
(47 reference statements)
12
78
0
2
Order By: Relevance
“…During these imaging experiments, only two cells underwent apoptosis, as marked by nuclear condensation followed by DNA fragmentation (data not shown). This low rate of apoptosis (1.8%) within the zebrafish retinal neuroepithelium is consistent with previous reports on fixed tissue (Biehlmaier et al, 2001). The paucity of cell death also confirmed that our imaging approach did not introduce phototoxicity.…”
Section: Diversity In Retinal Progenitor Interkinetic Nuclear Migrationsupporting
confidence: 92%
“…During these imaging experiments, only two cells underwent apoptosis, as marked by nuclear condensation followed by DNA fragmentation (data not shown). This low rate of apoptosis (1.8%) within the zebrafish retinal neuroepithelium is consistent with previous reports on fixed tissue (Biehlmaier et al, 2001). The paucity of cell death also confirmed that our imaging approach did not introduce phototoxicity.…”
Section: Diversity In Retinal Progenitor Interkinetic Nuclear Migrationsupporting
confidence: 92%
“…The numbers of TUNEL-positive cells in control retinas were very low at 36 hpf, 48 hpf, and 72 hpf (Figs. 3E, 3G, 3I, 3M), and on average, slightly lower than those reported by others (Biehlmaier et al, 2001;Cole & Ross, 2001). The numbers of TUNEL-positive cells in retinas of ethanoltreated embryos were only slightly greater (Fig.…”
Section: Ethanol Treatment Results In Modest Effects On Retinal Histomentioning
confidence: 51%
“…In the zebrafish, a series of cell-specific waves of apoptotic cell death has been documented to take place subsequent to the waves of cell birth (Biehlmaier et al, 2001). These waves of cell death follow the same sequence, with an initial wave of cell death in the ganglion cell layer followed by cell death in the inner and then outer nuclear layer.…”
Section: A Spatiotemporal Patternsmentioning
confidence: 99%